A Simple, Predictable Intraoral Technique for Retentive Mechanism Attachment of Implant Overdenture Attachments - Tony Daher, DDS, MSEd (Journal of Prosthodontics, 2003)
A technique is presented for intraorally attaching two O-ring attachments to a mandibular complete denture